Study on Relationship of Segmental Distribution of Coronary Artery Disease and Peripheral Arterial Disease - Habib, SM Ahsan; Hasan, Md Nazmul; Rahman, AKM Fazlur; Ahmed, Murshed; Fatema, Nilufar; Mahmood, Manzoor; Parvin, Tanzima; Alam, Md Mashiul; Noornabi, Md; Safiuddin, Mohammad; Siddique, Md Abu; Banerjee, Sajal Krishna; et al. (University Heart Journal, 2017)
Objectives: The purpose of this study was to investigate pattern and involvement of peripheral artery disease of lower limbs in patients suffering from clinically significant coronary artery disease. Methods: Total 58 patients with clinically diagnosed peripheral arterial disease of lower limb undergoing angiographic evaluation. Selective CAG in addition to peripheral arteriography was performed in all the study population as per ACC/AHA guidelines for CAG (class IIa recommendation). Result: In this study, It was found that the proportion of aorto-iliac disease was higher among the patients with coronary arterial disease (77.8%) and the association was statistically significant (p<0.05). Analysis found no statistically significant association between coronary arterial disease and Femo-popliteal and tibioperoneal vascular disease (p>0.05). Conclusion: Patients of coronary artery disease (CAD) are more likely to have severe peripheral arterial disease (PAD) involvement. Peripheral angiogram is useful tool in patient with CAD to detect previously undetected PAD and pattern of CAD reflects the severity and involvement of peripheral arteries. University Heart Journal Vol. 11, No. 2, July 2015; 68-70